Aplicaciones de la estimulación eléctrica de tejidos: revisión - Moreno Aranda, José Luis (Revista Mexicana de Ingenieria Biomedica, 2018)
In this article the various techniques and procedures of tissue electrical stimulation, known today, are reviewed. These areÑ muscular exercise, functional electrical stimulation, electroinduced analgesia, emptying and control of neurogenic bladders, parturition. Each one of these applications, is amply referenced in order to allow the interested reader to get additional information.